Examining normative values using the Cambridge neuropsychological test automated battery and developmental traits of executive functions among elementary school-aged children in Japan - Aoki, Sho; Nagatani, Fumiyo; Kagitani-Shimono, Kuriko; Ohno, Yuko; Taniike, Masako; Mohri, Ikuko (Frontiers in Psychology, 2023)
The Cambridge Neuropsychological Test Automated Battery (CANTAB) is a computerized and child-friendly neuropsychological assessment battery that includes subtests aimed at evaluating some aspects of executive functions. Using the CANTAB, this study aims to establish normative values based on the aspects of executive functions among school-aged children in Japan. The participants included 234 children (135 boys and 99 girls aged 6–12 years) enrolled in regular classes, without any clinical records of developmental disorders or educational support. The participants were grouped according to age (6–7, 8–9, and 10–12 years). Four CANTAB subtests, including spatial working memory (SWM) to assess spatial working memory, Stockings of Cambridge (SOC) to evaluate planning, intra/extradimensional set shift (IED) to evaluate attentional set shifting and flexibility, and stop signal task (SST) to evaluate inhibition, were administered to each participant. The results showed that performance in all the CANTAB subtests administered changed with age. Among the subtests, compared with performances in the SOC and IED, those in the SWM and SST improved earlier, thereby indicating that spatial working memory and inhibition develop earlier than planning as well as attentional set shifting and flexibility. Additionally, in the SST subtest, girls made fewer errors than boys did in the 6–7 years group. This study presents normative data of four CANTAB subtests according to age and sex among school-aged children in Japan. We expect that the findings will be used to develop effective tools for the early detection of and support for children with executive dysfunction.